Examining Ways in Which Youth Conferences Can Spell Out Gains in Community Youth Development and Engagement - Felicia C. Sanders; Marcela A. Movit; Dana L. Mitra; Danny F. Perkins (LEARNing Landscapes, 2007)
With student outcomes increasingly becoming associated witht est scores, schools are less able to dedicate themselves to helping students learn how to become engaged and active participants in a democracy. As a result, other community based organizations have stepped in to help students acquire the sense of agency, belonging, and competence—known as the "A, B, C’s" of youth development—that research has shown to be crucial for youth to become contributing citizens. Drawing on survey, interview and observational data, this paper considers how two such organizations give students an opportunity for personal development, while providing youth with leadership skills and opportunities to engage in their schools and communities. This research suggests that in addition to the traditional "A, B, C’s," it may be beneficial to consider aspects of diversity—proposed here as "D"—that play an important role in youth development, as well as the synergy of all four components of youth development that result in positive student outcomes.